Low‐frequency underwater sound generation by impacting transient cylindrical water jets - Kolaini, A; Roy, R; Crum, L; Mao, Y (Acoustical Society of America, 1993)
The impact of a jet of water onto a still‐water surface results in the entrainment of large amounts of air and the eventual formation of a bubble plume. Results from an experimental study of the noise produced by this process is presented. Preliminary results of this study were reported previously by Kolaini et al. [J. Acoust. Soc. Am. 89, 2452–2455 (1991)]. The densely populated bubble plumes were generated by dropping a fixed volume of water, held in a cylindrical container, onto a still‐water surface. High‐speed video images reveal the formation of a cylindrical bubble plume with a very high void fraction which grows in size until all the water is injected into the tank. As the leading end of the plume advances, a section of the plume separates near the crater region formed by the jet. After detachment, the separated plume, which is roughly spherical in shape, undergoes volume pulsations, and radiates relatively large‐amplitude, low‐frequency sound. The nature of the acoustic emissions from bubble plumes depends on the height of the water in the container, the container’s radius, and the velocity of the impacting jet. The natural frequency of oscillation of an individual bubble plume is inversely proportional to the radius of the plume and ranges from a few tens of Hz to over 100 Hz depending upon the void fraction of air contained within the plume. Results obtained with salt water as well as with rough jets are also discussed. The high‐speed video observations reveal that immediately following the bubble plume detachment, there is evidence of an axial jet directed downward into the bubble plume and an opposing jet directed upward into the crater formed by the impact. This jet appears to be the physical mechanism that drives the cloud into oscillation. Measurements indicate that the acoustic intensity radiated from bubble plumes correlate with the total potential energy of the water jet.